Optimal Remediation Scheme for a Wastewater Recharge Site: Contaminants Fate and Transport Model. Issue 6 (29th December 2017) - Rona, Michael; Lev, Ovadia; Gvirtzman, Haim
Abstract: A 3‐dimensional hydrologic groundwater flow and contaminant transport model was developed to address the feasibility and relevant time‐scales for remediation of a large soil aquifer treatment (SAT) site for domestic wastewater. The model accounted for a range of organic pollutant retardation factors and biodegradation kinetics. In order to detect the effect of the most retained and the most refracted/recalcitrant pollutants, it was crucial to model fractions of different properties rather than with average set properties. Four aquifer remediation scenarios, including two active washing procedures and two involving natural attenuation, were evaluated. The remediation efficiencies, in terms of residual plume size and mass of pollutant washout, were compared to each other and to the current operation scheme. According to the results, remediation mainly via natural attenuation rather than some form of intense pump and treat technology, is feasible, unlike the situation with hazardous waste sites. Enforced washout becomes less efficient with time due to increasing retardation of the residual pollutants. Therefore, pollution containment with natural biodegradation, which removed 95% of the emerging contaminants within 30 to 40 years was found to be the most valuable remediation scheme. Abstract : Article Impact Statement: Full remediation of a SAT site, including biodegradation kinetics and retarded organic compounds' influence, modeled.